Preparation and characterization of spherical yttrium iron garnet via coprecipitation - Jafelicci, M. [UNESP]; Godoi, R. H M [UNESP] (Elsevier, 2001)
The purpose of this work is to obtain spherical particles yttrium iron garnet (YIG) by coprecipitation technique. The spherical particles were obtained from either nitrate or chloride salt solutions by controlling the precipitation medium. Different agents of dispersion such as PVP and ammonium iron sulfate were used to optimize the shape and size of YIG. Samples were characterized by X-ray diffraction, scanning electron microscopy and vibrating sample magnetometry. The results show that the samples phase transition takes place at 850°C (orthorhombic phase) and at 1200°C (cubic phase). Spherical shape particles, with diameter of around 0.5 μm, present magnetization values close to the bulk value (26 emu g -1). © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Colloidal particles; Coprecipitations; Spherical yttrium iron garnet; YIG; Bulk value; Chloride salts; Colloidal particle; Coprecipitation technique; Cubic phase; Iron sulfates; Magnetization values; Orthorhombic phase; Shape and size; Spherical particle; Spherical shape; Vibrating sample magnetometry; Yttrium iron garnets; Ammonium compounds; Chlorine compounds; Coprecipitation; Garnets; Phase transitions; Scanning electron microscopy; Silicate minerals; Spheres; X ray diffraction; Yttrium; Yttrium compounds; Yttrium alloys